REFORMULASI HUKUM PERKAWINAN ISLAM DI INDONESIA - Agus Toni (Al Hikmah: Jurnal Studi Keislaman, 2016)
As social beings, humans can not live without any legal or sebutannya- name that regulate their social life. It is inconceivable there is a communion of life that knows no sort of order-in this case-law that will govern their lives. A belief that hold true Muslims is that Islam contained in the Quran and al-Sunnah is the guidance of Allah that must guide all his life for the salvation of the human race in the world and akhira.Berbeda case with teachings never before revealed by God, the teachings of Islam are not only applicable to a particular group of people and limited to a period tertentu.Ajaran Islam since revealed to have been established as a handbook for all human groups at various places and the time until the end of masa.Hal was affirmed by Ibn Qayim in his book "al-muwaqqi'in knows best," about the legal changes with the change of time, place, traditions and conditions. Although Islamic law, or Shari'ah is eternal as set forth in the teachings of the Qur'an and Sunnah, but human interpretation of Islamic law through the instrument of fiqh (jurisprudence) is flexible and responsive to the needs and problems of modern. Therefore reinterpretation is possible by keeping within the scope of the objectives of Shariah, so that excessive human activity can be prevented and foreign cultural elements can be removed. In the theory of Islamic law (fiqh fiqh), besides due to difference places and circumstances, changes to the law relies heavily on 'ilatul hukm (logical reason) behind their establishment. Similarly, the legal systems of the others, who live and act in various parts of the world are different, the Islamic legal system, especially family law, still exist and continue to apply Islamic world.